2016
DOI: 10.1016/j.psychres.2016.04.090
|View full text |Cite
|
Sign up to set email alerts
|

Childhood physical neglect promotes development of mild cognitive impairment in old age – A case-control study

Abstract: This study aimed to investigate the role of early traumatic experiences in development of mild cognitive impairment (MCI) in Chinese elderly people. Seventy six patients and 61 controls were selected and assigned into two study groups, MCI and control, respectively. Childhood Trauma Questionnaire-Short Form (CTQ-SF) was used for assessment of early trauma, episodic memory and association learning scales for memory evaluation. In addition, event-related potentials (ERPs) were measured using electroencephalograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 22 publications
0
24
4
1
Order By: Relevance
“…Recent clinical studies have further suggested that exposure to stress or trauma early in life might enhance the vulnerability to develop dementia later in life (Seifan et al, 2015 ; Wang et al, 2016 ), although the study of this hypothesis has only recently begun. The early-life period is a sensitive time for brain development, during which the brain is particularly vulnerable to adversities, that can alter developmental trajectories and lead to life-long changes in brain function (Heim and Nemeroff, 2001 ; Barker, 2004 ; Barker et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical studies have further suggested that exposure to stress or trauma early in life might enhance the vulnerability to develop dementia later in life (Seifan et al, 2015 ; Wang et al, 2016 ), although the study of this hypothesis has only recently begun. The early-life period is a sensitive time for brain development, during which the brain is particularly vulnerable to adversities, that can alter developmental trajectories and lead to life-long changes in brain function (Heim and Nemeroff, 2001 ; Barker, 2004 ; Barker et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The early-life period is a sensitive time for brain development, during which the brain is particularly vulnerable to adversities, that can alter developmental trajectories and lead to life-long changes in brain function (Heim and Nemeroff, 2001 ; Barker, 2004 ; Barker et al, 2013 ). In fact, early-life stress (ES) has been shown to induce deficits in adult hippocampal structure and functioning, as well as cognitive impairments in both humans and rodent ES models (Staff et al, 2012 ; Naninck et al, 2015 ; Wang et al, 2016 ; Calem et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Early-life stress (ES) has been associated with cognitive deficits in adulthood [1][2][3][4] and there is emerging evidence that ES also increases the risk for developing Alzheimer's disease (AD) [5,6]. For example, among children who have experienced physical neglect, mild cognitive impairment, considered a prodromal phase of AD, is more frequently observed [7]. Moreover, parental loss and stress during childhood have been associated with an increased risk of developing AD [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Early-life stress (ES) has been associated with cognitive deficits in adulthood [1][2][3][4] and there is emerging evidence that ES also increases the risk for developing Alzheimer's disease (AD) [5,6]. For example, among children who have experienced physical neglect, mild cognitive impairment, considered a prodromal phase of AD, is more frequently observed [7]. Moreover, parental loss and stress during childhood have been associated with an increased risk of developing AD [8][9][10].…”
Section: Introductionmentioning
confidence: 99%